Pewarisan Nilai-Nilai Kearifan Lokal Untuk Memproteksi Masyarakat Bali Dari Dampak Kemajuan Teknologi - Ni Luh Ketut Sukarniti (Jurnal Ilmiah Cakrawarti, 2020)
The importance of maintaining local wisdom for Balinese people in order to facevarious negative impacts of social changes brought about by .Technology The symptom, whichis basically felt by the Balinese today, is the fundamental socio-cultural change. The accelerationof the information coming along with the wave of technology has been significantly experiencedby the Balinese, both at the level of the “surface structure” (the attitudes and the pattern of behavior) and at the level of the “deep structure” (the value system, the life view, the philosophy,and the belief). The change is due to the culture contacts between countries in which there aredialectic fight between the contemporary values and those of the traditional where one tries totake the domination of another. Here, the hegemony and the neoliberal views are possiblycoming and breaking all the aspects of life, including the values of the local culture ever obeyedfirmly by the Balinese society. This condition leads to a spit and uncertain values situationbecause the people give more attention and respect to the modern values and marginalizethe transcendental values. This is resulting in various violations of the moral values reflected bythe feature, the style, and the life pattern of the society to occur. Therefore, reinforcement andinheritance of Balineselocal wisdom have to be conducted intensively to the Balinese youngergeneration.